Pyrene–nucleobase conjugates: synthesis, oligonucleotide binding and confocal bioimaging studies - Jabłoński, Artur; Fritz, Yannic; Wagenknecht, Hans-Achim; Czerwieniec, Rafał; Bernaś, Tytus; Trzybiński, Damian; Woźniak, Krzysztof; Kowalski, Konrad (Beilstein Journal of Organic Chemistry, 2017)
Fluorescent pyrene–linker–nucleobase (nucleobase = thymine, adenine) conjugates with carbonyl and hydroxy functionalities in the linker were synthesized and characterized. X-ray single-crystal structure analysis performed for the pyrene–C(O)CH2CH2–thymine (2) conjugate reveals dimers of molecules 2 stabilized by hydrogen bonds between the thymine moieties. The photochemical characterization showed structure-dependent fluorescence properties of the investigated compounds. The conjugates bearing a carbonyl function represent weak emitters as compared to compounds with a hydroxy function in the linker. The self-assembly properties of pyrene nucleobases were investigated in respect to their binding to single and double strand oligonucleotides in water and in buffer solution. In respect to the complementary oligothymidine T10 template in water, compounds 3 and 5 both show a self-assembling behavior according to canonical base–base pairing. However, in buffer solution, derivative 5 was much more effective than 3 in binding to the T10 template. Furthermore the adenine derivative 5 binds to the double-stranded (dA)10–T10 template with a self-assembly ratio of 112%. Such a high value of a self-assembly ratio can be rationalized by a triple-helix-like binding, intercalation, or a mixture of both. Remarkably, compound 5 also shows dual staining pattern in living HeLa cells. Confocal microscopy confirmed that 5 predominantly stains mitochondria but it also accumulates in the nucleoli of the cells.
Keywords: confocal microscopy; luminescence; nucleobases; oligonucleotide binding; pyrene; X-ray

(untitled) - Figueira-Duarte, T. M.; Müllen, K. (Chem. Rev., 2011)

(untitled) - Ciardelli, F.; Ruggeri, G.; Pucci, A. (Chem. Soc. Rev., 2013)

(untitled) - Breul, A. M.; Hager, M. D.; Schubert, U. S. (Chem. Soc. Rev., 2013)

(untitled) - Häner, R.; Garo, F.; Wenger, D.; Malinovskii, V. L. (J. Am. Chem. Soc., 2010)

(untitled) - Manicardi, A.; Guidi, L.; Ghidini, A.; Corradini, R. (Beilstein J. Org. Chem., 2014)

(untitled) - Astakhova, I. V.; Ustinov, A. V.; Korshun, V. A.; Wengel, J. (Bioconjugate Chem., 2011)

(untitled) - Østergaard, M. E.; Hrdlicka, P. J. (Chem. Soc. Rev., 2011)

(untitled) - Sau, S. P.; Madsen, A. S.; Podbevsek, P.; Anderson, N. K.; Kumar, T. S.; Andersen, S.; Rathje, R. L.; Anderson, B. A.; Guenther, D. C.; Karmakar, S.; Kumar, P.; Plavec, J.; et al. (J. Org. Chem., 2013)

(untitled) - Filichev, V. V.; Astakhova, I. V.; Malakhov, A. D.; Korshun, V. A.; Pedersen, E. B. (Chem. – Eur. J., 2008)

(untitled) - Teo, Y. N.; Kool, E. T. (Chem. Rev., 2012)

(untitled) - Ensslen, P.; Brandl, F.; Sezi, S.; Varghese, R.; Kutta, R.-J.; Dick, B.; Wagenknecht, H.-A. (Chem. – Eur. J., 2015)

(untitled) - Teo, Y. N.; Wilson, J. N.; Kool, E. T. (J. Am. Chem. Soc., 2009)

(untitled) - Korshun, V. A.; Manasova, E. V.; Balakin, K. V.; Malakhov, A. D.; Perepelov, A. V.; Sokolova, T. A.; Berlin, Y. A. (Nucleosides Nucleotides, 1998)

(untitled) - Beharry, A. A.; Lacoste, S.; O’Connor, T. R.; Kool, E. T. (J. Am. Chem. Soc., 2016)

(untitled) - Okamoto, A.; Tainaka, K.; Nishiza, K.-i.; Saito, I. (J. Am. Chem. Soc., 2005)

(untitled) - Ensslen, P.; Fritz, Y.; Wagenknecht, H.-A. (Org. Biomol. Chem., 2015)

(untitled) - Skorobogatyi, M. V.; Ustinov, A. V.; Stepanova, I. A.; Pchelintseva, A. A.; Petrunina, A. L.; Andronova, V. L.; Galegov, G. A.; Malakhov, A. D.; Korshun, V. A. (Org. Biomol. Chem., 2006)

(untitled) - St. Vincent, M. R.; Colpitts, C. C.; Ustinov, A. V.; Muqadas, M.; Joyce, M. A.; Barsby, N. L.; Epand, R. F.; Epand, R. M.; Khramyshev, S. A.; Valueva, O. A.; Korshun, V. A.; Tyrrell, D. L. J.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Ma, B.; Zeng, F.; Li, X.; Wu, S. (Chem. Commun., 2012)

(untitled) - Sezi, S.; Wagenknecht, H.-A. (Chem. Commun., 2013)

(untitled) - Trifonov, A.; Raytchev, M.; Buchvarov, I.; Rist, M.; Barbaric, J.; Wagenknecht, H.-A.; Fiebig, T. (J. Phys. Chem. B, 2005)

(untitled) - Wang, Z.; Zhang, D.; Zhu, D. (Anal. Chim. Acta, 2005)

(untitled) - Wang, Z.; Yu, Y.; Zhang, D.; Zhu, D. (Chin. Sci. Bull., 2006)

(untitled) - Kowalski, K.; Skiba, J.; Oehninger, L.; Ott, I.; Solecka, J.; Rajnisz, A.; Therrien, B. (Organometallics, 2013)

(untitled) - Kowalski, K.; Szczupak, Ł.; Saloman, S.; Steverding, D.; Jabłoński, A.; Vrček, V.; Hildebrandt, A.; Lang, H.; Rybarczyk-Pirek, A. (ChemPlusChem, 2017)

(untitled) - Skiba, J.; Schmidt, C.; Lippmann, P.; Ensslen, P.; Wagenknecht, H.-A.; Czerwieniec, R.; Brandl, F.; Ott, I.; Bernaś, T.; Krawczyk, B.; Szczukocki, D.; Kowalski, K. (Eur. J. Inorg. Chem., 2017)

(untitled) - Profft, E.; Döhler, I. (J. Prakt. Chem., 1962)

(untitled) - Wrona-Piotrowicz, A.; Zakrzewski, J.; Gajda, A.; Gajda, T.; Makal, A.; Brosseau, A.; Métivier, R. (Beilstein J. Org. Chem., 2015)

(untitled) - Kowalski, K.; Koceva-Chyła, A.; Pieniążek, A.; Bernasińska, J.; Skiba, J.; Rybarczyk-Pirek, A. J.; Jóźwiak, Z. (J. Organomet. Chem., 2012)

Modern Molecular Photochemistry of Organic Molecules - Turro, N. J.; Ramamurthy, V.; Scaiano, J. C. (University Science Books, 2010)

(untitled) - Hauke, F.; Hirsch, A.; Atalick, S.; Guldi, D. (Eur. J. Org. Chem., 2005)

(untitled) - Martin, R. L. (J. Chem. Phys., 2003)

(untitled) - Plasser, F.; Wormit, M.; Dreuw, A. (J. Chem. Phys., 2014)

(untitled) - Ensslen, P.; Gärtner, S.; Glaser, K.; Colsmann, A.; Wagenknecht, H.-A. (Angew. Chem., Int. Ed., 2016)

(untitled) - Baggaley, E.; Weinstein, J. A.; Williams, J. A. G. (Coord. Chem. Rev., 2012)

(untitled) - Xu, W.; Zeng, Z.; Jiang, J.-H.; Chang, Y.-T.; Yuan, L. (Angew. Chem., Int. Ed., 2016)

(untitled) - Dunn, W. K.; Kamocka, M. M.; McDonald, J. H. (Am. J. Physiol.: Cell Physiol., 2011)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Krishnan, R.; Binkley, J. S.; Seeger, R.; Pople, J. A. (J. Chem. Phys., 1980)

Gaussian 09W, 8.0 (Gaussian, Inc., 2009)

CrysAlis CCD and CrysAlis RED (Oxford Diffraction, Oxford Diffraction Ltd, 2008)

(untitled) - Clark, R. C.; Reid, J. S. (Acta Crystallogr., Sect. A: Found. Crystallogr., 1995)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 2008)

(untitled) - Spek, A. L. (Acta Crystallogr., Sect. D, 2009)

(untitled) - Farrugia, L. J. (J. Appl. Crystallogr., 1997)

(untitled) - Macrae, C. F.; Edington, P. R.; McCabe, P.; Pidcock, E.; Shields, G. P.; Taylor, R.; Towler, M.; van de Streek, J. (J. Appl. Crystallogr., 2006)